ANALISIS EKSERGI PADA PEMBANGKIT LISTRIK TENAGA UAP - , PUJI SRI NINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Until 2012, steam power plant supplies 44.02 % of national electricity demand. Most of steam power plants use fossil fuels as an energy source that are not renewable and limited. The use of fossil fuels also generates greenhouse gases. Exergy evaluation is made based on the second law of thermodynamics. It is a method that can be used in design, evaluation, optimization, and construction of thermal power systems. Exergy analysis can be used to determine the amount and location of plant componentsâ inefficiency. Exergy analysis on power plant is required to identify opportunities in each plant component that can be used to perform optimization in power plant components. In this research, a power plant system is modelled using Cycle Tempo. The model consists of fuel and vapor cycle .The model is simulated to get the exergy efficiency value and to count the exergy losses of systemâs main components. The values obtained are used as a basis for recommendations on power plant optimization. The net exergy efficiency of the modeled power plant is 35.92%. The results showed that 87% of the total exergy losses occurred in the system is mainly contributed by three components which are boilers, combustion chamber, and reheater. High exergy losses is occurred in boiler with the amount of 356 MW, combustion chamber with the amount of 218 MW and reheater with the amount of 206 MW. Optimization can be performed on those three components to suppress its exergy losses but based on consideration of technological aspects, the possibility to optimize the boiler and reheater is very small while optimization on the combustion chamber is still possible to do